2012
DOI: 10.1016/j.nbt.2011.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of monobodies that bind specifically to the SH3 domain of the Fyn tyrosine protein kinase

Abstract: Fyn is a non-receptor protein tyrosine kinase that belongs to a highly conserved kinase family, Src family kinases (SFKs). Fyn plays an important role in inflammatory processes and neuronal functions. To generate a synthetic affinity reagent that can be used to probe Fyn, a phage-display library of fibronectin type III (FN3) monobodies was affinity selected with the SH3 domain of Fyn and three binders were isolated. One of the three binders, G9, is specific in binding to the SH3 domain of Fyn, but not to the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 58 publications
1
41
0
Order By: Relevance
“…5F). Though this hit rate may seem low, the G9 monobody inhibitor, which has an excellent K D for Fyn SH3 (166 nM) 29 , inhibited the D-Tau–Fyn SH3 interaction to a similar degree. Therefore, the fact that several compounds with distinct chemotypes show activity in this stringent assay that requires cell permeability, resistance to cellular degradation, non-toxicity, and high potency is very promising.…”
Section: Resultsmentioning
confidence: 99%
“…5F). Though this hit rate may seem low, the G9 monobody inhibitor, which has an excellent K D for Fyn SH3 (166 nM) 29 , inhibited the D-Tau–Fyn SH3 interaction to a similar degree. Therefore, the fact that several compounds with distinct chemotypes show activity in this stringent assay that requires cell permeability, resistance to cellular degradation, non-toxicity, and high potency is very promising.…”
Section: Resultsmentioning
confidence: 99%
“…Their ability to target individual domains within endogenous proteins should allow determination of the role of those domains in protein function and signalling cascades. An example of this is shown by SBPs that have been selected against SH3 and SH2 domains for several members of the Src family of proteins [38][39][40][41][42]. This family of non-receptor tyrosine kinases has nine members, Src, Yes, Fyn, Fgr, Yrk, Lyn, Blk, Hck, and Lck, that contain both SH2 and SH3 binding domains in addition to their kinase domain and an SH4 domain [59].…”
Section: Src Signallingmentioning
confidence: 99%
“…Monobody reagents have been identified that bind with high specificity and nM affinities to either the SH3 or the SH2 domains within several family members, notably Src, Fyn, Lyn and Lck, [38][39][40][41][42]. The majority of the SH3-binding reagents contained the classical proline-rich SH3 binding motif xxPxxP whereas the SH2 binding reagents were strongly antagonistic to the substrate pYEEI, but did not show a consensus sequence [38][39][40][41][42]. Interestingly, specificity was greater for the SH3 monobody that lacked the consensus sequence, whilst the binder displaying the highest affinity showed a degree of cross-reactivity to a number of family members, namely Yes, Fyn, Lyn and Lck [41].…”
Section: Src Signallingmentioning
confidence: 99%
See 1 more Smart Citation
“…Not only have they been utilized for affinity reagent generation, but also to improve protein stability (Pershad, 2012), generate inhibitors (Huang, 2012), provide insight into potential protein binding interactions (Halperin, 2003), and rapidly map transcription factor-DNA interactions (Freckleton, 2009). As the technology continues to develop, the opportunities involving phage display will as well.…”
Section: Commentarymentioning
confidence: 99%